A Novel Tigecycline Adjuvant ML-7 Reverses the Susceptibility of Tigecycline-Resistant Klebsiella pneumoniae - Sun, Lilan; Sun, Lang; Li, Xue; Hu, Xinxin; Wang, Xiukun; Nie, Tongying; Zhang, Youwen; You, Xuefu (Frontiers in Cellular and Infection Microbiology, 2022)
The increasing incidence of tigecycline resistance undoubtedly constitutes a serious threat to global public health. The combination therapies had become the indispensable strategy against this threat. Herein, 11 clinical tigecycline-resistant Klebsiella pneumoniae which mainly has mutations in ramR, acrR, or macB were collected for tigecycline adjuvant screening. Interestingly, ML-7 hydrochloride (ML-7) dramatically potentiated tigecycline activity. We further picked up five analogs of ML-7 and evaluated their synergistic activities with tigecycline by using checkerboard assay. The results revealed that ML-7 showed certain synergy with tigecycline, while other analogs exerted attenuated synergistic effects among tigecycline-resistant isolates. Thus, ML-7 was selected for further investigation. The results from growth curves showed that ML-7 combined with tigecycline could completely inhibit the growth of bacteria, and the time-kill analysis revealed that the combination exhibited synergistic bactericidal activities for tigecycline-resistant isolates during 24 h. The ethidium bromide (EtBr) efflux assay demonstrated that ML-7 could inhibit the functions of efflux pump. Besides, ML-7 disrupted the proton motive force (PMF) via increasing ΔpH, which in turn lead to the inhibition of the functions of efflux pump, reduction of intracellular ATP levels, as well as accumulation of ROS. All of which promoted the death of bacteria. And further transcriptomic analysis revealed that genes related to the mechanism of ML-7 mainly enriched in ABC transporters. Taken together, these results revealed the potential of ML-7 as a novel tigecycline adjuvant to circumvent tigecycline-resistant Klebsiella pneumoniae.